Deposition characteristics of small-molecule CBP:PBD:TPD:Ir(mppy)3 organic thin films using a modified electrospray deposition method. (25th February 2016) - Niinuma, Yoshiki; Takatsuka, Yusuke; Terada, Ryo; Ueda, Hiroyuki; Kikuchi, Akihiko
Abstract: The development of a solution-based technique for the deposition of small-molecule organic thin films is desirable for the advancement of organic devices. In this study, we investigated the deposition characteristics of an organic thin film deposited by modified electrospray deposition with three typical spraying modes: Taylor cone, convergent jet, and multijet. The results indicate that the multijet mode can generate the smallest droplets with the narrowest size distribution. Using the multijet mode, we deposited a pinhole-free, smooth CBP:PBD:TPD:Ir(mppy)3 small-molecule organic film with a root-mean-square surface roughness of 2.5 nm.